Differentiation and CRISPR-Cas9-mediated genetic engineering of human intestinal organoids - Adriana Martinez-Silgado; Fjodor A. Yousef Yengej; Jens Puschhof; Veerle Geurts; Charelle Boot; Maarten H. Geurts; Maarten B. Rookmaaker; Marianne C. Verhaar; Joep Beumer; Hans Clevers (STAR Protocols, 2022)
Summary: Intestinal organoids are three-dimensional cultures that resemble key aspects of the epithelium of origin. Here, we describe how to differentiate human small intestinal organoids by combining growth media variations and genetic engineering. We detail the differentiation of human intestinal organoids in the presence and absence of BMP agonists to recapitulate a broader scope of functional cell states found in vivo. Using transient overexpression of the transcription factor Neurogenin-3, we describe the enhancement of differentiation toward rare enteroendocrine cells.For complete details on the use and execution of this protocol, please refer to Beumer et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.